Inflammasome-mediated glucocorticoid resistance: The receptor rheostat. (2nd January 2016) - Paugh, Steven W.; Bonten, Erik J.; Evans, William E.
ABSTRACT: In primary acute lymphoblastic leukemia cells exhibiting de novo resistance to glucocorticoids, we recently discovered decreased promoter methylation of caspase 1 ( CASP1 ) and NLR family, pyrin domain containing 3 ( NLRP3 ), which resulted in increased transcription, constitutive NALP3 (NACHT, LRR and PYD domains-containing protein 3) inflammasome activation, and caspase 1-mediated cleavage of the glucocorticoid receptor. This revealed a novel mechanism of glucocorticoid resistance that was recapitulated in model systems.